2016
DOI: 10.1371/journal.pcbi.1004796
|View full text |Cite
|
Sign up to set email alerts
|

BIITE: A Tool to Determine HLA Class II Epitopes from T Cell ELISpot Data

Abstract: Activation of CD4+ T cells requires the recognition of peptides that are presented by HLA class II molecules and can be assessed experimentally using the ELISpot assay. However, even given an individual’s HLA class II genotype, identifying which class II molecule is responsible for a positive ELISpot response to a given peptide is not trivial. The two main difficulties are the number of HLA class II molecules that can potentially be formed in a single individual (3–14) and the lack of clear peptide binding mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…6c-e). This limitation is consistent with the fact that presentation of antigens is essential but not sufficient for induction of robust T cell responses 51,55,58 (Supplementary Note 2). Therefore, by combining deep learning 59 and large-scale T cell response data, we envision that a future method will provide refined predictions for the immunogenicity of HLA ligands, whether autoantigens relevant for autoimmunity, alloantigens relevant to transplantation or as vaccine candidates relevant for diverse applications.…”
Section: Discussionsupporting
confidence: 75%
“…6c-e). This limitation is consistent with the fact that presentation of antigens is essential but not sufficient for induction of robust T cell responses 51,55,58 (Supplementary Note 2). Therefore, by combining deep learning 59 and large-scale T cell response data, we envision that a future method will provide refined predictions for the immunogenicity of HLA ligands, whether autoantigens relevant for autoimmunity, alloantigens relevant to transplantation or as vaccine candidates relevant for diverse applications.…”
Section: Discussionsupporting
confidence: 75%
“…While the case for host-dependent selection pressure is a difficult one to make for Bp, it is noteworthy that p6, a T cell epitope highlighted in the present study, as in our earlier work, was found to have been deleted from a pathogenic, clinical isolate from Cambodia 14 . Although the Bp immunome is clearly large and complex, the definition of highly immunodominant, common, peptide-HLA complexes offers the potential for developments in future immune monitoring of immune status 12 14 , 22 , 23 . A new tool developed from analysis of Bp pMHC and Pseudomonas aerguniosa 24 pMHC complexes in responder datasets is BIITE, a means of elucidating likely pMHC combinations out of bulk PBMC responses in HLA-heterozygous individuals who will be expressing multiple HLA class II heterodimers to present peptide 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the Bp immunome is clearly large and complex, the definition of highly immunodominant, common, peptide-HLA complexes offers the potential for developments in future immune monitoring of immune status 12 14 , 22 , 23 . A new tool developed from analysis of Bp pMHC and Pseudomonas aerguniosa 24 pMHC complexes in responder datasets is BIITE, a means of elucidating likely pMHC combinations out of bulk PBMC responses in HLA-heterozygous individuals who will be expressing multiple HLA class II heterodimers to present peptide 23 . AhpC, and specifically, the p6 epitope from this antigen, stand out as a part of the Bp immunome that is highly visible to the T cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we use the master equation (19) for the evolution of the probability density p t (σ), to derive dynamical equations for the macroscopic parameters m(σ) = (m 1 (σ), . .…”
Section: Appendix Kramers-moyal Expansion Of the Master Equationmentioning
confidence: 99%
“…However, they normally ignore microscopic details and stochasticity, due to noise in the biological environment or fluctuations in cellular densities, and generally require the estimation of a large number of unknown parameters. Agent-based simulations [12][13][14][15] and machine learning approaches [16][17][18][19] have been successful in incorporating statistical noise and microscopic information (e.g. cellular interactions, antibodies sequences etc), however, they usually require more significant computational efforts.…”
Section: Introductionmentioning
confidence: 99%